EVALUASI PENETAPAN PAJAK HOTEL DAN PAJAK BUMI DAN BANGUNAN PADA BPPRD KOTA METRO - Virra Yulian Putri; Yulita Zanaria; Angga Kurniawan (Jurnal Akuntansi AKTIVA, 2021)
This study aims to determine the Determination of Hotel Tax and Land and Building Tax at BPPRD Metro City. Data is obtained from the results of hotel tax data, land and building tax (PBB) data, local revenue data (PAD) for the period 2017-2019. The data analysis of this research was carried out using qualitative analysis. The results of this study indicate that the hotel tax and land and building tax target plans compiled by the BPPRD and stipulated in plenary meetings to determine targets for each fiscal year based on regional needs can be seen that for three consecutive years the target set has experienced a significant increase. This shows that the government's efforts to increase regional income in Regional Original Revenue through hotel taxes and land and building taxes for rural and urban areas are already good. The targets that have been set are submitted to the relevant agencies and then look at the potentials that can be explored, especially related to the management of hotel taxes and land and building taxes in achieving the target. Keywords: Hotel Tax, Land and Building Tax, Local Revenue